A Study Of Health Status Of Rural Population Of Mohagaon Village - Hiwakar P.A; Aswar N.R; Agrawal V.K (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the health status of rural people? Objective: To study the nutritional status and morbidity pattern in rural people. Setting: Mohagaon village Study design: cross-sectional Participants: All subjects from Mohagaon village. Statistical analysis: studentâ€s test. Study variables: Age, sex, family type, religion, height, weight, haemoglobin, protein and calorie intake, morbid conditions etc. Results: Out of 850 individualsâ€ surveyed, 53.1% were males while 46.9% were females. There were total 176 families of which 120 (68.2%) were nuclear, 17(9.7%) were joint and 39(22.1%) were extended families. 63.1% were Hindus and 36.9% were Buddhists. Mean height and weight of males and females in all age groups up to 21 years was less than 1, C.M.R. standards. Mean haemoglobin values of individuals in different age groups were significantly lower than the values recommended by WHO. 83.33% families were taking proteins and calories less than the required amount. Some of the morbid conditions found in this rural population were anaemia(22.58%), vit-A deficiency (12.47%), dental caries(12.23%), amoebiasis(10%), vit B-complex deficiency(9.76%), P.E.M. (8.46%), Vit. D deficiency (7.29%), worm infestation (6%) and diarrhoea(5.41%) etc.